Does land abundance explain African institutions? - James Fenske (Yale University, Economic Growth Center, 2009)
I show how abundant land and scarce labor shaped African institutions before colonial rule. I present a model in which exogenous suitability of the land for agriculture and endogenously evolving population determine the existence of land rights, slavery, and polygyny. I then use crosssectional data on pre-colonial African societies to demonstrate that, consistent with the model, the existence of land rights, slavery, and polygyny occurred in those parts of Africa that were the most suitable for agriculture, and in which population density was greatest. Next, I use the model to explain institutions among the Egba of southwestern Nigeria from 1830 to 1914. While many Egba institutions were typical of a land-abundant environment, they sold land and had disputes over it. These exceptions were the result of a period of land scarcity when the Egba first arrived at Abeokuta and of heterogeneity in the quality of land.
Keywords: N57; O10; 330; Africa; institutions; land rights; slavery; polygyny